Closed-Loop Implantable Therapeutic Neuromodulation Systems Based on Neurochemical Monitoring - Mirza, Khalid B.; Golden, Caroline T.; Nikolic, Konstantin; Toumazou, Christofer (Frontiers in Neuroscience, 2019)
3 Closed-loop or intelligent neuromodulation allows adjustable, personalised neuromodulation 4 which usually incorporates recording of some biomarker, followed by implementation of an 5 algorithm which decides the timing (when ?) and strength (how much ?) of stimulation. 6 Closed-loop neuromodulation has been shown to have greater benefits compared to open loop 7 neuromodulation, particularly for therapeutic applications such as pharmacoresistant epilepsy, 8 movement disorders and potentially for psychological disorders such as depression or drug 9 addiction. However, an important aspect of the technique is selection of an appropriate, preferably 10 neural biomarker. Neurochemical sensing can provide high resolution biomarker monitoring for 11 various neurological disorders as well as provide deeper insight into neurological mechanisms. 12 The chemicals of interest being measured, could be ions such as potassium (K+), sodium 13 (Na+), calcium (Ca2+), chloride (Cl􀀀), hydrogen (H+) or neurotransmitters such as dopamine, 14 serotonin, glutamate. This review focusses on the different building blocks necessary for a 15 neurochemical, closed-loop neuromodulation system such as biomarkers, sensors and data 16 processing algorithms. Furthermore, it also highlights the merits and demerits of using this 17 biomarker modality.